Low Back Pain and Associated Imaging Findings among HIV‐Infected Patients Referred to an HIV/Palliative Care Clinic. Issue 3 (13th September 2013) - Molony, Elizabeth; Westfall, Andrew O.; Perry, Brian A.; Tucker, Rodney; Ritchie, Christine; Saag, Michael; Mugavero, Michael; Sullivan, Joseph C.; Merlin, Jessica S.
Abstract Background Low back pain is a common cause of chronic pain in human immunodeficiency virus (HIV)‐infected patients. The American College of Physicians and American Pain Society guidelines for diagnostic imaging in low back pain are difficult to apply to patients with chronic illnesses like HIV who may have risk factors for cancer or compression fractures, but whether imaging all such patients for low back pain improves outcomes is unknown. Objective Our objective was to describe patients referred to a chronic pain‐focused HIV/palliative care clinic (HPCC) with back pain and their associated lumbar spine imaging findings. Methods We conducted a retrospective chart review of patients at a palliative care clinic that sees patients with HIV, most of whom have chronic pain. Charts with a diagnosis of low back pain were cross‐referenced with an imaging database and any magnetic resonance imaging (MRI) of the lumbar spine with or without contrast were identified. Results Seventy‐six of 137 patients referred to the HPCC were found to have back pain. These patients were mainly young (median age 45, interquartile range 40–51) with well‐controlled HIV. Twenty‐two (29%) of these patients had an MRI of the lumbar spine, and 11 (50%) of these warranted follow‐up, most of whom had degenerative disc disease, including four with findings concerning for malignancy. Discussion This is the first study to explore the role of spinal imaging in HIV‐infected patients. In our study, four patients had findings concerning for malignancy. These findings suggest that spinal imaging should be considered in the work up of HIV‐infected patients with moderate to severe back pain.